Punctuations how the arts think the political - Shapiro, Michael J. (Duke University Press, 2019)
"In Punctuations Michael J. Shapiro examines how punctuation--conceived not as a series of marks but as a metaphor for the ways in which artists engage with intelligibility--opens pathways for thinking through the possibilities for oppositional politics. Drawing on Theodor Adorno, Alain Robbe-Grillet, and Roland Barthes, Shapiro demonstrates how punctuation's capacity to create unexpected rhythmic pacing makes it an ideal tool for writers, musicians, filmmakers, and artists to challenge structures of power. In works ranging from film scores and jazz compositions to literature, architecture, and photography, Shapiro shows how the use of punctuation reveals the contestability of dominant narratives in ways that prompt readers, viewers, and listeners to reflect on their acceptance of those narratives. Such uses of punctuation, he theorizes, offer models for disrupting structures of authority, thereby fostering the creation of alternative communities of sense from which to base political mobilization"--